PERSEPSI WISATAWAN TERHADAP ATRAKSI WISATA BUDAYA DI RUMAH GODANG DESA KOTO SENTAJO KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Heri Rouli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Cultural tourism in Kuantan Singingi Regency, Riau Province is one of potential tourism object that worthy to introduce to the tourists who will make tourism travel to Kuantan Singingi. One of the cultural attractions in Kuantan Singingi is Rumah Godang, Koto Sentajo Village. The purpose of this study is to determine perception of tourists to the cultural tourism attractions in Rumah Godang Koto Sentajo Village, Kuantan Singingi, which became one of the tourism object that based on culture and it was one of cultural heritage that is still preserved by society or Kuantan Singingi District Government. This study used a qualitative method with descriptive approach to to examine the issues raised. The subject of research consists of proposive sampling which produces 3 key informants and accidental sampling which produces 5 informants. While data collection techniques in this study using observation, interviews and documentations. Based on the research that has been done, the perception of tourists to the cultural tourism attractions in Rumah Godang Koto Sentajo Village, Kuantan Singingi has had a historical interest, architectural interest, traveler comfort, convenience services, architectural beauty, material beauty and historical development. However, Rumah Godang as a tourism object that has cultural tourism attractions are still not maximal in providing information about the history and cultural objects and the management nor promotion that still have to be improved in order to Rumah Godang more widely known by tourists. Keywords: Perception, Tourists, Rumah Godang, Koto Sentajo Village, Kuantan Singingi Regency